Production technology adoption and electronic market participation intensity of chilli (dry) farmers in India: Application of triple-hurdle model - K. Nirmal Ravi Kumar; S. N. Mishra; Adinan Bahahudeen Shafiwu; Shailendra N. Gajanan; Suresh Chandra Babu; A. Sandhya Neelima (Cogent Economics & Finance, 2023)
Agricultural and food system transformation helps increase farm productivity and encourages farmers to participate in updated value chains, adopt newer technologies, thereby helping farmers transform their livelihoods in a sustainable manner. Relatedly, value chain innovations depend on multiple decisions farmers make at various stages of the value chain, adequate participation being a primary factor. In this paper, we integrate farmers' adoption decision of a new variety of chilli crop ("Teja") along with their electronic market participation decision and e-market participation intensity, based on data from the chilli farming sector in India, where agricultural markets have been modernized through digitization (Kalgudi e-Market). Thus, the employed Triple-Hurdle Model (THM) integrates adoption decision of "Teja" variety of chilli, e-Market Participation Decision and e-market participation intensity thereby, allowing us to make inferences relating to chilli farmers in Andhra Pradesh, India. Our results, showed that the drivers of "Teja" variety adoption, e-market participation, and e-participation intensity include education, reliable extension services, access to seeds of high yielding varieties, market information, and membership in farmer-producer organizations. Added to these, personnel training visits, prompt deliveries of inputs, and prompt payment of sales proceeds are also important in influencing participation and intensities. Results show that the three stochastic decisions of THM are strongly correlated implying that the adoption decision of "Teja" variety of chilli by the farmers influences the e-market participation decision and consequently, e-market participation intensity and these three decisions are sequential. On the contrary, the decisions viz., e-market participation decision and e-market participation intensity as input buyers and consequent adoption of "Teja" variety of chilli are simultaneous. So, the policy measures that promote production technology interventions (say, "Teja" variety of chilli) will definitely enhance better e-market access of chilli farmers. Accordingly, the breeding programs of the agricultural research stations should enhance the uptake of improved varieties in tune with modern marketing (e-market) technologies. Future farm policy and agricultural-research and innovations must recognize the potential that the digital marketing systems have to offer. Such considerations coupled with the provision of market infrastructure including assaying, grading, storage, and market information will promote digital transformation in agricultural value chains in developing countries like India.
Keywords: C51; C81; M31; Q13; Q18; 330; Adoption; chilli; e-market participation decision; market participation intensity; production technology; triple-hurdle mode